Fostering Autonomous Learning Through Peer Feedback - Ema Wilianti Dewi; Siti Roki'ah (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
Peer assessment appeared in social constructionism theory since peer assessment activity involves the joint construction of knowledge through discourse. This study focuses on one product that arises from peer-assessment activity: feedback from peers. Besides, this study linked peer feedback from the peer-assessment activity and learners' autonomy in language learning. Autonomous learning is regarded as a desirable goal in an educational context. In exploring this issue, the study used the case study method. The first-semester students in an academic writing class in the English language teaching department at a university in Indonesia are the participants in this study. The researchers qualitatively analyze students' feedback from the peer-assessment process and conduct follow-up interviews to answer how peer feedback from peer-assessment activity fosters students' autonomous learning. The results show that peer assessment could engage the students with their peers in giving and receiving feedback. Furthermore, giving feedback to peers requires students to have prior and new knowledge that must be studied independently. In responding to peer feedback, the students believe that peer feedback is essential in fostering their autonomy. Educational practitioners may use this assessment for junior to higher education students to activate their autonomous learning.